2009
DOI: 10.1002/jctb.2291
|View full text |Cite
|
Sign up to set email alerts
|

Separation of p‐xylene from ternary xylene mixture using silicalite‐1 membrane: process optimization studies

Abstract: BACKGROUND: The design of experiments (DoE) is applied to the process optimization of p-xylene (pX) separation from its isomers m-xylene (mX) and o-xylene (oX) mixture using silicalite-1 membrane supported on α-alumina. A central composite design (CCD) coupled with response surface methodology (RSM) was used to correlate the effect of two separation process variables, temperature (150-250• C) and pX feed partial pressure (0.10-0.26 kPa) to three responses: (i) pX flux; (ii) pX/oX separation factor; and (iii) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…This can be done by introducing functional groups to the structure of zeolite including surfaces and pores. [11][12][13] The modied zeolites then show better catalytic activity, acidity, and selectivity in a series of importantly industrial reactions and processes. Yeong et al 11 successfully introduced 3-mercaptopropyltrimethoxysilane into the silicalite-1 pore-structure by using in situ deposition method and subsequently oxidized to sulfonic acid silicalite-1 membrane.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be done by introducing functional groups to the structure of zeolite including surfaces and pores. [11][12][13] The modied zeolites then show better catalytic activity, acidity, and selectivity in a series of importantly industrial reactions and processes. Yeong et al 11 successfully introduced 3-mercaptopropyltrimethoxysilane into the silicalite-1 pore-structure by using in situ deposition method and subsequently oxidized to sulfonic acid silicalite-1 membrane.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] The modied zeolites then show better catalytic activity, acidity, and selectivity in a series of importantly industrial reactions and processes. Yeong et al 11 successfully introduced 3-mercaptopropyltrimethoxysilane into the silicalite-1 pore-structure by using in situ deposition method and subsequently oxidized to sulfonic acid silicalite-1 membrane. The sulfonated silicalite-1 membrane was acting as a membrane with high selectivity and applicable to combined separation and reaction processes.…”
Section: Introductionmentioning
confidence: 99%
“…Zeolite films and membranes have been widely studied during the past two decades. They could be applied to separation membranes for their uniform molecular pore size, [1][2][3][4] membrane reactors for their catalytic activity, 5 microprocessor insulator materials for their low dielectric constant, [6][7][8] and corrosion resistant coatings for their excellent chemical and thermal stability. 9,10 In a MFI crystal, the 0.53 Â 0.56 nm straight channels (b-axis) are interconnected with 0.51 Â 0.55 nm sinusoidal channels (a-axis).…”
mentioning
confidence: 99%
“…Therefore, b-oriented MFI films are of great interest from the viewpoint of both fundamental study and practical applications, though most of the zeolite films reported are randomly oriented. [3][4][5]11 In situ crystallization and secondary growth are two major methods to synthesize b-oriented MFI films. The advantage of the former is its simplicity, but some a-oriented MFI crystals always exist.…”
mentioning
confidence: 99%